2015
DOI: 10.5455/ijtrr.000000105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Active Cycle of Breathing Technique on Functional Capacity in Patient With Bronchiectasis

Abstract: Back ground and Purpose: Bronchiectasis is associated with impairment of the mucociliary escalator and retention of secretions within the bronchial tree, making airway clearance a primary concern in the management of bronchiectasis. Patients and methodology: Objective: The objective of this study was to determine the effect of active cycle of breathing as an airway clearance technique on functional capacity in adults with productive bronchiectasis by using six minute walk test and dyspnea index. Design: The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, the magnitude of change noted as d= 0.205 which implied that there is a small clinical change observed in the treatment group. A similar study was conducted by Elsayed et al [59] on 45 bronchiectasis patients to evaluate the effect of ACBT on functional capacity using the 6MWT. In this study ACBT was administered 3 times a week for 2 months and it concluded that this technique shows significant and remarkable improvement in the functional capacity in bronchiectasis patients.…”
Section: Discussionmentioning
confidence: 93%
“…However, the magnitude of change noted as d= 0.205 which implied that there is a small clinical change observed in the treatment group. A similar study was conducted by Elsayed et al [59] on 45 bronchiectasis patients to evaluate the effect of ACBT on functional capacity using the 6MWT. In this study ACBT was administered 3 times a week for 2 months and it concluded that this technique shows significant and remarkable improvement in the functional capacity in bronchiectasis patients.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, Elsayed. et al (2015) (24) and Taha et.al, (2021) (13) clarified that chest physiotherapy improved oxygen saturation and promoted normal results of arterial blood gases . In relation to spirometric values, the findings of the present study showed that there were significant statistical differences regarding FVC, FEV1, and FEV1/FVC among control and study groups on the 3 rd day post ACBT.…”
Section: Concerning Comparison Between Control and Study Groups In Re...mentioning
confidence: 98%
“…(25) This result was in the same direction as Zisi et al, (2022) (27) who concluded that ACBT is a method that has been found to be effective in increasing sputum removal from the airway. Additionally ,Elsayed et al, (2015) (24) mentioned that the application of ACBT helps to clean the airways from the excessive secretion. Moreover, Zhong et al, (2021) (28) who demonstrated that ACBT is an effective approach for significantly increased sputum wet weight in study group.…”
Section: Concerning Comparison Between Control and Study Groups In Re...mentioning
confidence: 99%
“…Wahyudi al., (2021) [34] comes in line in study of Active Cycle of Breathing to Respiratory Rate in Patients with Lung Tuberculosis, cleared that the mean respiration rate scores before ACBT was more than that after intervention. Elsayed et al, (2015) [11] mentioned that The Active Cycle of Breathing Technique (ACBT) can clean the airways so that respiratory rate is reduced and the breathing pattern improves. Breathing Control which can prevent bronchospasm and oxygen desaturation, Thoracic Expansion Exercise can help loosen and clear sputum and improve collateral ventilation, and the last exercise, the Forced Expiratory Technique, can remove sputum by pressing the thorax and airway.…”
Section: Concerning Application Of Active Cycle Of Breathingmentioning
confidence: 99%